2024
DOI: 10.3847/2041-8213/ad24f3
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Fan-spine Magnetic Topology through Flux Emergence and Subsequent Jet Production

Yadan Duan,
Hui Tian,
Hechao Chen
et al.

Abstract: Fan-spine magnetic structure, as a fundamental three-dimensional topology in magnetic reconnection theory, plays a crucial role in producing solar jets. However, how fan-spine configurations form in the solar atmosphere remains elusive. Using the Chinese Hα Solar Explorer (CHASE) and the Solar Dynamics Observatory, we present a case study on the complete buildup of fan-spine topology driven by flux emergence and the subsequent jet production. Two fan-spine structures and the two associated null points are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 105 publications
1
1
0
Order By: Relevance
“…When the filament lifts at 04:25 UT, an inner bright patch can be identified in Figure 2(b2). These characteristics suggest that the filament is situated within a fan-spine magnetic field configuration, as suggested by previous works (e.g., Shen et al 2019b;Yang et al 2020b;Zhou et al 2021a;Duan et al 2022Duan et al , 2024. The filament flux reconnects with and releases or a kink-like instability of the stressed internal closed field (e.g., Pariat et al 2009;Karpen et al 2017) and subsequently erupts, forming a jet along the magnetic field lines, as shown in the 304 and 131 Å sequence images in Figure 3.…”
Section: August 28supporting
confidence: 74%
See 1 more Smart Citation
“…When the filament lifts at 04:25 UT, an inner bright patch can be identified in Figure 2(b2). These characteristics suggest that the filament is situated within a fan-spine magnetic field configuration, as suggested by previous works (e.g., Shen et al 2019b;Yang et al 2020b;Zhou et al 2021a;Duan et al 2022Duan et al , 2024. The filament flux reconnects with and releases or a kink-like instability of the stressed internal closed field (e.g., Pariat et al 2009;Karpen et al 2017) and subsequently erupts, forming a jet along the magnetic field lines, as shown in the 304 and 131 Å sequence images in Figure 3.…”
Section: August 28supporting
confidence: 74%
“…Considering the three-dimensional (3D) scenario, with the aid of magnetic field extrapolation techniques and high-resolution observations, an increasing number of studies revealed that the 3D magnetic configuration of the coronal jets is a fan-spine structure (Shen 2021). This structure is composed of a null point, a dome-shaped fan, and the inner (outer) spines located inside (outside) the fan, which is typically accompanied by a circular flare ribbon and an inner bright patch (e.g., Masson et al 2009;Wang & Liu 2012;Li et al 2017Li et al , 2018Shen et al 2019b;Hou et al 2019;Lee et al 2020;Duan et al 2022Duan et al , 2024Huang et al 2024;Zhang 2024). In a high-resolution MHD simulation, Wyper et al (2017Wyper et al ( , 2018 showed a breakout model (Antiochos et al 1999) for coronal jets in a 3D fan-spine structure involving small filaments.…”
Section: Introductionmentioning
confidence: 99%